Behaviour of piles proceedings of the conference organized by the Institution of Civil Engineers in London, 15-17 September 1970. (Institution of Civil Engineers, 1971)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a conference held in September 1970.